Production of glucose from cassava starch: Statistical approach - Noorulnajwa Diyana, Yaacob; Ku Syahidah, Ku Ismail; Khairul Farihan, Kasim; Mohamed Zulkali, Mohamed Daud, Prof. Madya Dr. (2011)
Organized Universiti Malaysia Perlis (UniMAP), 12th - 13th December 2009 at Dewan Tun Dr. Ismail A, Putra World Trade Centre (PWTC), Kuala Lumpur, Malaysia.